In utero adenine base editing corrects multi-organ pathology in a lethal lysosomal storage disease - Sourav K. Bose (Nature Portfolio, 2021)
Lysosomal storage diseases like mucopolysaccharidosis type I (MPS I) cause pathology before birth and result in early morbidity and mortality. Here, the authors show that in utero base editing mediates multi-organ phenotypic and survival benefits in a mouse model recapitulating a common human MPSI mutation.